Rule of the Gun in Sugarland
Shot and produced entirely in the Philippines by WITNESS partner Joey Lozano in collaboration with the NAKAMATA indigenous coalition. The video documents in chilling detail a period of three months in late 2001 when three indigenous leaders were murdered, others attacked, and a village razed as coalition members peacefully and legally pursued ancestral land claims on the island of Mindanao in the Philippines. During this whole period, Joey Lozano was working with NAKAMATA, a new WITNESS partner, conducting camera trainings and providing support. Even as police and authorities failed to act, these WITNESS partners were on the scene in the immediate aftermath of attacks - documenting, gathering evidence, interviewing and recording the scene of the crime. Footage included in this video was also shown on the top Philippine investigative TV show and provided as evidence to investigators.